Investigation and Production of Furniture for Villa Tugendhat 2009–2012 - Ambroz, Miroslav (Docomomo Journal, 2012)
Villa Tugendhat is an expression of “gesamtkunstwerk”, where every detail is subordinated to the whole. Mies van der Rohe devoted the same amount of attention to the furnishings of the house as to its design. The furniture designed and placed according to his conception is such an important aspect of the house that without it the Villa is only half complete. The system governing the organization of all parts of the building – ratios, proportions, whole areas and details – is visible also in the precise placement of the house contents, which only allowed the owner limited variability in the use of space. The Villa became world famous not long after its completion, but Fritz and Grete Tugendhat were not destined to spend many happy years there. Even before the Munich Pact had been signed, signifying the de facto end of democratic Czechoslovakia, they left Brno forever. At the end of the summer of 1938 two removal vans came to take part of the furnishings to St. Gallen in Switzerland. Today the main body of the original equipment is, except for several pieces, still in the possession of the family. The Villa was, after two years of general reconstruction, reopened to the public in February this year. For the first time since 1938 it was equipped with all the furnishings Mies van der Rohe had designed for it. The most significant event was the return after seventy years of the original curved wall of the dining area to its original location. This famous Makassar wall had been considered lost for many decades.